Biogeographical patterns of community-level content of N and P and their stoichiometric ratios in subtropical forest floor bryophytes. (October 2022) - Wang, Zhe; Feng, Defeng; Liu, Xin; Hu, Bin; Bao, Weikai
Graphical abstract: Highlights: Biogeographical patterns of nutrients for bryophytes remain largely unknown. Relationships between bryophyte nutrients and environmental factors were calculated. Bryophyte N and P content increased with increasing elevations and decreasing MAT. Nutrient content of bryophytes and those of soil were positively associated. Soil nutrient content and MAT were more important determinants of bryophyte N and P. Abstract: With special phylogenetic status, life history, morphology, adaptations, and ecophysiological strategies, bryophytes differ from vascular plants in terms of the requirement, uptake, allocation, and releasing rate of nutrients. However, biogeographical patterns of nutrients for bryophytes remain largely unknown. The present study determined and calculated the community-level carbon (C), nitrogen (N), and phosphorus (P) content and their stoichiometric ratios of the photosynthetic tissues of the subtropical forest-floor bryophytes collected from 295 sites in Sichuan province, China. We aimed to find out: 1) the geographical patterns in the content of N and P and the stoichiometric ratio of N to P for bryophytes; 2) the effects of environmental factors (climate, soil nutrient content, and stand attributes); and 3) the driving factors. We found that the bryophytes collected from the western plateau had a higher P content and a lower N:P than those from the eastern basin. The bryophytes' N and P content generally increased with increasing elevations and decreasing mean annual temperature (MAT) and potential evaporation, while the N:P ratio decreased with decreasing elevations. But these patterns were scale-dependent. Nutrient content of bryophytes and those of soil were positively associated. Bryophyte N content was unrelated to mean annual precipitation (MAP) and stand attributes, while P content was negatively related to MAP and shrub and herb cover. Among the environmental factors at play, soil nutrient content and MAT were more important determinants of bryophyte N and P content than MAP and stand attributes. This study contributes to a better understanding of the relationships among environmental factors and bryophyte N and P at a basin-mountain transition zone and provides evidence to quantitatively assess the ecological role of bryophytes in nutrient cycling in the ecosystem.